1999
DOI: 10.1111/j.1749-6632.1999.tb07642.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible Pathogenetic Relevance of Interleukin‐1β in “Destructive” Organ‐specific Autoimmune Disease (Hashimoto's Thyroiditis)

Abstract: Thyroid follicular cells (TFC) abundantly express a variety of immunologically relevant surface molecules in Hashimoto's thyroiditis (HT), for example, MHC antigens and adhesion molecules such as ICAM-1. Cytokines produced by infiltrating type 1 helper and cytotoxic T cells are importantly involved in de novo expression or up-regulation of such molecules. We recently demonstrated that TFC from HT patients almost invariably bear on their surface two additive functional molecules: Fas/Apo1/CD95, an important par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 10 publications
1
19
0
1
Order By: Relevance
“…Not surprisingly, considering the implication of T cell-mediated cytotoxic processes in the pathogenesis of Hashimoto's thyroiditis after the lymphoid infiltration of the thyroid, the proinflammatory cytokines IL-1␤, IL-6, and IL-8 have all been shown to be expressed in the thyroids of patients suffering from the disease (26,(33)(34)(35)(36). This report shows that these cytokines are expressed in the thyroids of OS chickens before the onset of the lymphoid infiltration.…”
Section: Discussionmentioning
confidence: 64%
“…Not surprisingly, considering the implication of T cell-mediated cytotoxic processes in the pathogenesis of Hashimoto's thyroiditis after the lymphoid infiltration of the thyroid, the proinflammatory cytokines IL-1␤, IL-6, and IL-8 have all been shown to be expressed in the thyroids of patients suffering from the disease (26,(33)(34)(35)(36). This report shows that these cytokines are expressed in the thyroids of OS chickens before the onset of the lymphoid infiltration.…”
Section: Discussionmentioning
confidence: 64%
“…On the other hand, we expected that genetic producibility of IL-1b may also relate to the severity of HD, because IL-1b induces the expression of some chemokines and surface molecules on thyrocytes in vitro and seems to enhance the inflammatory destruction of thyrocytes [35][36][37]. However, the IL-1b -31C/T polymorphism was not associated with the severity of HD (Table 1), suggesting no association between the genetic producibility of IL-1b and the severity of HD.…”
Section: Discussionmentioning
confidence: 99%
“…18 ± 23 Regulation of death receptor pathways in the thyroid may be a potential mechanism in which inflammatory cytokines might act to promote disease progression. Several groups, including our own, have shown the influence of inflammatory cytokines in Fas-mediated apoptosis of cultured thyroid cells 11,12,24,25 and reviewed in Borgerson et al 14 We have also shown that thyroid epithelial cells (TECs) are susceptible to TRAIL-mediated apoptosis after pretreatment with cycloheximide (CHX) and that TRAIL itself is expressed by the TECs treated with IFNg, TNFa or IL1b. 26 Combined, this data suggests that TRAIL-mediated apoptosis may have a role in autoimmune thyroiditis.…”
Section: Introductionmentioning
confidence: 91%